2022
DOI: 10.1007/s11356-022-22496-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tourism development upon environmental sustainability: a suggested framework for sustainable ecotourism

Abstract: The empirical research investigated the relationship between tourism development and environmental suitability to propose a framework for sustainable ecotourism. The framework suggested a balance between business and environmental interests in maintaining an ecological system with the moderating help of government support and policy interventions. The study population encompasses tourism stakeholders, including tourists, representatives from local communities, members of civil administration, hoteliers, and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(92 citation statements)
references
References 65 publications
0
88
0
4
Order By: Relevance
“…The social capital in question is in the form of mutual aid and deliberation as a form of local wisdom (30). Business people who can listen to the aspirations of the community are shown by the action of involving villagers as their business workforce (32). Thus, community participation to support ecotourism management and planning can be achieved (33).…”
Section: Hypothesis Analysismentioning
confidence: 99%
“…The social capital in question is in the form of mutual aid and deliberation as a form of local wisdom (30). Business people who can listen to the aspirations of the community are shown by the action of involving villagers as their business workforce (32). Thus, community participation to support ecotourism management and planning can be achieved (33).…”
Section: Hypothesis Analysismentioning
confidence: 99%
“…Thirdly, Baloch et al (2022) argued that development for tourism infrastructure and land use often burdens NC through over-consumption, leading to soil erosion, augmented pollution, loss of natural habitats, and endangered species. More specifically, in a study of 'over-tourism' in Venice, Seraphim et al (2018) suggested that economics and culture are inextricably linked to the conflict between human and natural capital.…”
Section: Natural Capital In Tourism and Hospitalitymentioning
confidence: 99%
“…Despite the benefits, it is evident that an overwhelming rise in tourism (i.e., RTM) may have detrimental effects on a country (Razzaq et al, 2023 ; Yang et al, 2023 ). For example, environmental damage resulting from the exploitation of tourism resources (Baloch et al, 2023 ) and/or increase in energy consumption and human-induced production, transportation, rapid urbanization, and industrial development are widely recognized negative consequences of unrestrained RTM growth (De Siano & Canale, 2022 ; Shinde & Olsen, 2022 ; Tabash et al, 2023 ). Therefore, it is essential to comprehend the extent to which tourism, specifically the RTM, assures a good contribution and the point at which it begins to conflict with development.…”
Section: Introductionmentioning
confidence: 99%